Antimicrobial effects of surface pre-reacted glass-ionomer (S-PRG) eluate against oral microcosm biofilm - Garcia, Maíra Terra [UNESP]; Namba, Andressa Mayumi [UNESP]; do Carmo, Paulo Henrique Fonseca [UNESP]; Pedroso, Lara Luise Castro [UNESP]; de Lima, Patrícia Michele Nagai [UNESP]; Gonçale, Juliana Caparroz [UNESP]; Junqueira, Juliana Campos [UNESP] (Taylor & Francis, 2024)
This study investigated the antimicrobial activity of surface pre-reacted glass ionomer eluate (S-PRG) against oral microcosm biofilms collected from the oral cavity of patients. Dental biofilm samples were collected from three volunteers to form microcosm biofilms in vitro. Initially, screening tests were carried out to determine the biofilm treatment conditions with S-PRG eluate. The effects of a daily treatment for 5 min using three microcosm biofilms from different patients was then evaluated. For this, biofilms were formed on tooth enamel specimens for 120 h. Biofilms treated with 100% S-PRG for 5 min per day for 5 days showed a reduction in the number of total microorganisms, streptococci and mutans streptococci. SEM images confirmed a reduction in the biofilm after treatment. Furthermore, S-PRG also reduced lactic acid production. It was concluded that S-PRG eluate reduced the microbial load and lactic acid production in oral microcosm biofilms, reinforcing its promising use as a mouthwash agent.